A multicenter, randomized, double-blind trial of a new porcine surfactant in premature infants with respiratory distress syndrome - Rebello, Celso Moura (Einstein (Sao Paulo), 2014)
OBJECTIVE: To compare the efficacy and safety of a new porcine-derived pulmonary surfactant developed by Instituto Butantan with those of animal-derived surfactants commercially available in Brazil, regarding neonatal mortality and the major complications of prematurity in preterm newborns with birth weight up to 1500g and diagnosed with respiratory distress syndrome. METHODS: Neonates diagnosed with respiratory distress syndrome were randomized to receive either Butantan surfactant (Butantan group) or one of the following surfactants: Survanta(®) or Curosurf(®). Newborns receiving Survanta(®) or Curosurf(®) comprised the control group. The main outcome measures were mortality rates at 72 hours and at 28 days of life; the typical complications of prematurity as evaluated on the 28th day of life were defined as secundary outcomes. RESULTS: No differences were observed between the Butantan (n=154) and control (n=173) groups in relation to birth weight, gestational age, sex, and prenatal use of corticosteroids, or in mortality rates both at 72 hours (14.19% versus 14.12%; p=0.98) and at 28 days (39.86% versus 33.33%; p=0.24) of life. Higher 1- and 5-minute Apgar scores were observed among control group newborns. No differences were observed as regards the secondary outcomes, except for greater need for supplemental oxygen and a higher incidence of interstitial pulmonary emphysema in the Butantan group. CONCLUSION: The mortality rates at 72 hours and 28 days of life and the incidence of major complications of prematurity were comparable to those found with the animal-derived surfactants commercially available in Brazil, showing the efficacy and safety of the new surfactant in the treatment of respiratory distress syndrome in newborns.